INFLUENCE OF POLICY AUDITING OVER PROCUREMENT-ON-PROCUREMENT PERFORMANCE IN PUBLIC HEALTH FACILITIES IN KAKAMEGA COUNTY, KENYA - Nyaranga , Barrack Ochieng; Ouma, Dennis (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
The procurement statute in addition to regulations, gives a variety of guidelines aimed at the entire tendering method. Even though public procurement having put in place to help direct the procurement functions in public establishments, certain domestic procurement dynamics have an impact on the variables that determine public procurement acquiescence and procurement performances within public health facilities. Thus, the purpose of the study was to establish the influence of policy auditing over procurement-on-procurement performance in public health facilities in Kakamega County, Kenya. It adopted a descriptive survey research design, with a target population of 346 individuals, including 12 Sub-County Directors of Health, 167 hospital superintendents, and 167 procurement officials. As the study’s target population was small, it sampled the whole population. Accordingly, the study’s sample processes used the census approach. The researcher collected data using questionnaires and interview guides. The instruments were validated by specialists in the area of study. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) analyzed for the two scores and was found to be 0.79, therefore, the instruments were reliable. Quantitative data was analyzed using descriptive and inferential statistics, and presented in tables, while, qualitative data was analyzed using the common themes, qualitative data extracted, organized, and then discussed under the main objective areas of the study. This was later presented using quotations. The study established that there is a statistically significant association between procurement audit activities like policy auditing, audit of procedures, audit of processes and audit of controls over procurement and procurement performance in public health facilities. It was therefore recommended that there should be consideration of policy auditing, audit of procedures, audit of processes and audit of controls over procurement. The information provided by this research will benefit policymakers, community members and academicians.